PERKEMBANGAN SISTEM HUKUM DAGANG INDONESIA DALAM KONTEKS BISNIS GLOBAL - Retna Gumanti (Prosiding Seminar Nasional Indonesia, 2026)
Indonesia's trade law system has undergone significant changes in line with the increasing integration of the global economy and the transformation of modern business, including the development of digital trade. This research aims to analyze the development of Indonesia's commercial law system in the context of global business and its implications for modern business activities. The research method is a qualitative approach based on library research, including the review of scientific literature, regulations, and reports from relevant international institutions. The results of the study show that trade regulation reform, business licensing simplification, and adaptation to the digital economy are important factors in increasing national business competitiveness. However, there are still challenges in the form of regulatory complexity, overlapping policies, and the effectiveness of legal implementation that need improvement. This research emphasizes the importance of strengthening legal institutions and harmonizing trade regulations with international standards to support sustainable business growth in the era of economic globalization.